Dissipative Catalysis with a Molecular Machine. (21st June 2019) - Biagini, Chiara; Fielden, Stephen D. P.; Leigh, David A.; Schaufelberger, Fredrik; Di Stefano, Stefano; Thomas, Dean
Abstract: We report on catalysis by a fuel‐induced transient state of a synthetic molecular machine. A [2]rotaxane molecular shuttle containing secondary ammonium/amine and thiourea stations is converted between catalytically inactive and active states by pulses of a chemical fuel (trichloroacetic acid), which is itself decomposed by the machine and/or the presence of additional base. The ON‐state of the rotaxane catalyzes the reduction of a nitrostyrene by transfer hydrogenation. By varying the amount of fuel added, the lifetime of the rotaxane ON‐state can be regulated and temporal control of catalysis achieved. The system can be pulsed with chemical fuel several times in succession, with each pulse activating catalysis for a time period determined by the amount of fuel added. Dissipative catalysis by synthetic molecular machines has implications for the future design of networks that feature communication and signaling between the components. Abstract : Ein Nichtgleichgewichtszustand einer molekularen Maschine wird für die Katalysesteuerung verwendet. Ein Rotaxan wird vorübergehend durch CCl3 CO2 H von einem katalytisch inaktiven Zustand in eine aktive Form umgewandelt. Deprotonierung durch das Rotaxan fördert die Decarboxylierung der Säure, was das System in seinen Ursprungszustand zurücksetzt und die Katalyse stoppt. Dies ermöglicht die temporale Kontrolle einer gekoppelten biomimetischen Reduktion.